Pemetaan Resistensi Nyamuk Aedes sp Terhadap Malation dan Kepadatan Vektor Demam Berdarah Dengue (DBD) di Sulawesi Utara - Steven Jacub Soenjono; Suwarja Suwarja; Joy Victor Imanuel Sambuaga (Jurnal Sehat Mandiri, 2020)
The event of mosquito immunity or resistance to malation is one of the main inhibitors of chemical eradication of vectors with insecticides. Vector resistance to insecticides is a global phenomenon, especially for managers of vector-borne control programs in Indonesia. The aims of this study was to map the resistance of Aedes sp mosquitoes to the malation and vector density of Dengue Hemorrhagic Fever (Aedes sp) in North Sulawesi Province in 2019. This research was descriptive in order to obtain a description of pre-adult vector density and to map the status of Dengue Hemorrhagic Fever vector resistance (Aedes sp) against malation. Resistance status data using data from 2015-2018 research. The population in this study are houses in North Minahasa Regency, Minahasa Regency, Tomohon City, Bitung City and Manado City. The sample for vector density is a larva survey of 100 resident houses which includes case houses and houses around DHF cases. North Minahasa Regency (Wautumou Village), Minahasa Regency (Papakelan Village), Tomohon City (Rurukan Village), Bitung City (Girian Permai Village), Manado City (Malalayang Village 2). Determination of the sample based on the highest case in each district in the city during the DHF vector resistance test in 2015-2018. The results showed that the average density of HI vectors (31.%), BI (17.5) and CI (34.8%) with resistance status in the four districts of the mosquito vector city of DHF were resistant and one district (North Minahasa) with a vulnerable status. Resistance and density vectors are digitally mapped.